1975
DOI: 10.1115/1.3423663
|View full text |Cite
|
Sign up to set email alerts
|

Stress Concentrations at the Apex of a Plane Indenter Acting on an Elastic Half Plane

Abstract: The singular stress field at the vicinity of the apex of an elastic plane indenter of various angles compressing an elastic half plane was studied by using a complex variable technique. Three particular cases where the indenter is perfectly bonded, slips or adheres according to the Coulomb’s law of friction, to the half plane were considered. The characteristic equations for the determination of the order of the stress singularity at the vicinity of the apex of the indenter for the above three cases were defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 0 publications
2
71
0
1
Order By: Relevance
“…It is subject to a normal force P, possibly a moment M and a shearing force Q, and any of these may vary in time in an arbitrary way. The state of stress adjacent to a slipping corner for such a problem has been studied in detail by Gdoutos and Theocaris [1], but the question that is asked here is: 'What is the minimum value of the coefficient of friction to guarantee adhesion, in the neighbourhood of the contact corner A?' The most obvious way to approach the problem is to solve for the interfacial contact pressure distribution and the shear traction distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It is subject to a normal force P, possibly a moment M and a shearing force Q, and any of these may vary in time in an arbitrary way. The state of stress adjacent to a slipping corner for such a problem has been studied in detail by Gdoutos and Theocaris [1], but the question that is asked here is: 'What is the minimum value of the coefficient of friction to guarantee adhesion, in the neighbourhood of the contact corner A?' The most obvious way to approach the problem is to solve for the interfacial contact pressure distribution and the shear traction distribution.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the singularity in stresses was never stronger than the inverse square root of the distance d, and it had no oscillatory multiplier corresponding to complex zeros of the characteristic determinant. The study was extended to a contact with the Coulomb law of dry friction by Gdoutos and Theocaris [7], Comninou [5] and, in more detail, by Churchman, Mugadu and Hills [4]. Still no complex roots was found, whereas the singularity in stresses appeared depending on the slip direction and could be stronger than O(1/ √ d).…”
Section: Fig 1 Interface Leyers With Finite Thickness Near An Commonmentioning
confidence: 96%
“…For this class of problems further contributions are due to Dundurs [11], Bogy and Wang [12], Hein and Erdogan [13], Dundurs and Lee [14], Gdoutos and Theocaris [15], Theocaris and Gdoutos [16], and Rao [17]. The case of an TV-material composite wedge was treated by Dempsey and Sinclair [18], [19].…”
Section: Introductionmentioning
confidence: 99%